The Effectiveness of Digital Literacy in Economic Learning - Prasetyo, P. Eko; Anggraeni, Oki (Dinamika Pendidikan, 2020)
The purpose of this research is to increase students’ economic learning interest and outcomes using digital literacy technology, such as Sparkol Video Scribe (SVc) and media chart (MC). This is an experimental research comprising of the control and treatment classes with international trade discussed as a sub-topic of the economic material. The learning activities method used the ADDIE model. While, the research subjects are high school students in Central Java. N-Gain model was used to determine the most effective level of analysis as well as the modification and path analysis. The main results showed that the application of SVc and MC learning models can attract students' interest in economic learning well. Although the SVc application was not effective in improving their overall performance, the MC literacy model was still effective. However, students' interest in learning about the second model has not been able to improve its performance significantly. The results further showed that the digital literacy method was not always able to improve student learning and performance effectively and efficiently.